Ecophysiology of Moringa oleifera Lam in function of different rainfall conditions - Santiago, Margaret Thatcher Barros; Bezerra Neto, Egídio (Revista Geama, 2017)
Drought conditions cause behavioral changes in plants, which proportions vary according to genotype, duration, severity and stage of development. One of their defense strategies is the accumulation of organic solutes, decreasing their osmotic potential to absorb water. This study aimed to compare the levels of photosynthetic pigments and soluble proteins in Moringa oleifera Lam plants grown in different rainfall conditions. Moringa leaves were collected in Recife-PE, with 227 mm.month-¹ as average month rainfall during plant growth and in Pirauá, with 87 mm.month-¹ in the same period, located at Natuba-PB. Solutes were quantified from leaf extraction in 80% acetone, followed by analysis at wavelengths 447, 595, 645 and 663 nm. Data were submitted to ANOVA and means were compared by Tukey test (p <0.05). Moringa extracts from Pirauá presented the lowest chlorophyll b content; therefore carotenoid and soluble proteins concentration was higher than the extracts from Recife. Moringa oleifera plants grown in sites with lowest rainfall regime may have their higher soluble proteins and carotenoids accumulation as a physiological adaptation to prolonged water scarcity.